2019
DOI: 10.21203/rs.2.11659/v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Spatio-temporal variation of malaria hotspots in central Senegal, 2008-2012

Abstract: Background In malaria endemic areas, identifying spatio-temporal hotspots is becoming an important element of innovative control strategies targeting transmission bottlenecks. The aim of this work was to describe the spatio-temporal variation of malaria hotspots in central Senegal, and to identify the meteorological, environmental, and preventive factors that influence this variation. Methods The weekly incidence of malaria cases recorded from 2008 to 2012 in 575 villages of central Senegal (total populatio… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2020
2020
2020
2020

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 46 publications
(71 reference statements)
0
2
0
Order By: Relevance
“…An alternative could be the importation of diverse genotypes due to human or mosquito mobility 21,[27][28][29][30] . A similar study of malaria incidence and prevalence has demonstrated the existence of malaria transmission hotspots at the village level in Senegal 7,8 . In such villages, human density, human behavior, lax malaria bed-net use, substandard housing construction, and a favorable ecological environment for mosquito proliferation (presence of mosquito breeding sites) have all been identified as risk factors for a household to be in a hotspot 31 .…”
Section: Discussionmentioning
confidence: 81%
See 1 more Smart Citation
“…An alternative could be the importation of diverse genotypes due to human or mosquito mobility 21,[27][28][29][30] . A similar study of malaria incidence and prevalence has demonstrated the existence of malaria transmission hotspots at the village level in Senegal 7,8 . In such villages, human density, human behavior, lax malaria bed-net use, substandard housing construction, and a favorable ecological environment for mosquito proliferation (presence of mosquito breeding sites) have all been identified as risk factors for a household to be in a hotspot 31 .…”
Section: Discussionmentioning
confidence: 81%
“…Targeting and eliminating malaria hotspots can play an important role in malaria elimination 3,6 . Different studies using conventional malaria epidemiologic tools such as malaria incidence and prevalence rates, malaria morbidity and mortality rates, and entomological inoculation rates (EIR) have identified hotspots of malaria transmission; however, some of these metrics are better suited for more highly endemic regions [7][8][9] and may become less useful as malaria transmission declines. As some regions strive for malaria elimination, along with the decline of the disease incidence some of these conventional malaria metrics may become less informative 10 .…”
Section: Introductionmentioning
confidence: 99%